Construction of a Sequencing Library from Circulating Cell‐Free DNA. Issue 1 (1st April 2016) - Fang, Nan; Löffert, Dirk; Akinci‐Tolun, Rumeysa; Heitz, Katja; Wolf, Alexander
Abstract: Circulating DNA is cell‐free DNA (cfDNA) in serum or plasma that can be used for non‐invasive prenatal testing, as well as cancer diagnosis, prognosis, and stratification. High‐throughput sequence analysis of the cfDNA with next‐generation sequencing technologies has proven to be a highly sensitive and specific method in detecting and characterizing mutations in cancer and other diseases, as well as aneuploidy during pregnancy. This unit describes detailed procedures to extract circulating cfDNA from human serum and plasma and generate sequencing libraries from a wide concentration range of circulating DNA. © 2016 by John Wiley & Sons, Inc.